2018
DOI: 10.2147/cmar.s155923
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of hsa_circ_0011946 suppresses the migration and invasion of the breast cancer cell line MCF-7 by targeting RFC3

Abstract: IntroductionAlthough some circRNAs have been found to regulate the progression of malignancies, their functions and coupled molecular mechanisms are still unclear. In our study, we sought to assess the underlying molecular mechanisms of circRNAs in breast cancer and therefore explored the differentially expressed circRNAs and co-expression networks, followed by in vitro experiments.Materials and methodsHigh-throughput RNA sequencing was performed to obtain an unbiased profile of circRNA expression. CircRNA-miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…21 Studies have shown that abnormal circRNAs are involved in tumorigenesis and disease progression. 22 25 However, whether they are general cancer biomarkers or cancer specific biomarkers is not clear. To distinguish the differentially expressed circRNAs between ESCC and BC, we performed a comparative study.…”
Section: Discussionmentioning
confidence: 99%
“…21 Studies have shown that abnormal circRNAs are involved in tumorigenesis and disease progression. 22 25 However, whether they are general cancer biomarkers or cancer specific biomarkers is not clear. To distinguish the differentially expressed circRNAs between ESCC and BC, we performed a comparative study.…”
Section: Discussionmentioning
confidence: 99%
“…it is also upregulated in Triple-negative breast cancer (TNBC) [64]. Since expression inhibition of this gene at both mRNA and protein level suppresses the migratory and invasive ability of MCF-7 cell lines [65], this gene would be a therapeutic target for colorectal cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, has-circ-0011946 is significantly up-regulated in breast cancer and different breast cancer cell lines. The expression of has-circ-0011946 is positively correlated with RFC3 expression, silencing of has_circ_0011946 inhibits migration and invasion of MCF-7 cell [ 77 ].…”
Section: Mechanism and Function Of Circrnas In Cancermentioning
confidence: 99%